CRYPTOCURRENCY IN ISLAMIC ECONOMIC PRINCIPLES - Ahmad Nouruzzaman; Abdul Wahab; Abdul Hamid Habbe (Dinasti Publisher, 2021)
Islam as a religion that is flexible, dynamic and adaptive to the times. However, this certainly has ethical limitations and has the principle that values ??in Islamic teachings must be the basis in every human activity, especially in community activities or muamalah. Therefore, this paper aims to critically describe cryptocurrency investment in Islamic economic principles.The method used in this paper is a scientific study approach with literature study, with data collection through the study of books, literature, notes, and various reports related to the problem to be solved. Based on the results of this study, cryptocurrency when viewed in Islamic economic principles does not meet the criteria as a medium of exchange and investment that is permitted in Islam. Cryptocurrencies at the beginning of their creation had a clear goal, a complicated system that was not acceptable to everyone. So that cryptocurrency can be manipulated and monopolized by certain parties. In addition, cryptocurrencies have high volatility so they are very volatile and are closer to gambling.